2021
DOI: 10.1371/journal.pone.0246243
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of complete postnatal care services and its determinants among rural women in Southern Ethiopia: Community-based cross-sectional study based on the current WHO recommendation

Abstract: Background Postnatal care services are a constellation of preventive care, practices, and assessments designed to identify and manage maternal and newborn complications during the first six weeks after birth. Recognizing the role of the appropriate PNC at this critical time, the World Health Organization recommended four visits as a complete PNC for all post-partum mothers and newborns to ensure their survival. Although there have been numerous studies on the factors affecting the general PNC service in Ethiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 23 publications
1
18
1
Order By: Relevance
“…We found that 85.6% of both the women and their neonates had at least one PNC contact, and this was associated with both individual and health system/policy factors. Although, slightly lower than the 90% level of PNC coverage recommended by WHO [ 28 ], it is higher than the reported prevalence of 48.4% for Malawi, 63% for Zambia and 78.4% for Indonesia [ 29 31 ]. This level of utilisation is commendable and should be further supported by government interventions, aimed at providing free maternal and child health services through the FHCI project.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…We found that 85.6% of both the women and their neonates had at least one PNC contact, and this was associated with both individual and health system/policy factors. Although, slightly lower than the 90% level of PNC coverage recommended by WHO [ 28 ], it is higher than the reported prevalence of 48.4% for Malawi, 63% for Zambia and 78.4% for Indonesia [ 29 31 ]. This level of utilisation is commendable and should be further supported by government interventions, aimed at providing free maternal and child health services through the FHCI project.…”
Section: Discussionmentioning
confidence: 73%
“…Similarly, in this study the odds of PNC utilisation were higher among woman who had eight or more ANC contacts compared to their counterparts who had fewer. This may be attributed to the fact that regular contact with health workers during ANC, accords more opportunities for education and counselling about the need to seek for health care services during and after pregnancy [ 28 , 31 , 38 ]. Mothers who had at least one visit by a health field worker had higher odds of PNC utilisation, a finding similar to that of other studies done in similar contexts [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is lower than the reported prevalence of 48.4% for Malawi, 63% for Zambia and 78.4 % for Indonesia [26][27][28]. This observed PNC utilisation is lower than the 90% recommended PNC coverage by WHO [29], which continues to limit the early identi cation of postpartum complications among the women and the newborns in the country. This situation is particularly worrying because about 40% of the reported maternal and perinatal morbidity and mortality occur in the immediate postpartum period.…”
Section: Resultsmentioning
confidence: 77%
“…Similarly, in this study the odds of PNC utilisation were two times higher among woman who had eight or more ANC contacts compared to their counterparts who had fewer. This may be attributed to the fact that regular contact with health workers during ANC, accords more opportunities for education and counselling about the need to seek for health care services during and after pregnancy [28, 29,34]. However, there is need to explore the mechanisms associated with increased odds of PNC utilisation among women who initiate ANC after the rst trimester.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation